The Small Time Asymptotics of SPDEs with Reflection - Juan Yang; Jianliang Zhai; Qing Zhou (Abstract and Applied Analysis)
We study stochastic partial differential equations with singular drifts and with reflection, driven by space-time white noise with nonconstant diffusion coefficients under periodic boundary conditions. The existence and uniqueness of invariant measures is established under appropriate conditions. As a byproduct, the Hölder continuity of the solution is obtained. The strong Feller property is also obtained. Moreover, we show large deviation principle.